Comprehensive Analysis of circRNA-miRNA-mRNA Network in Cervical Squamous Cell Carcinoma by Integrated Analysis - Wu Q (OncoTargets and Therapy, 2020)
Qiongwei Wu, Ping Liu, Guoying Lao, Yu Liu, Wenying Zhang, Chengbin Ma Gynecology Department, Changning Maternity and Infant Health Hospital, Shanghai, People’s Republic of ChinaCorrespondence: Ping Liu; Chengbin MaGynecology Department, Changning Maternity and Infant Health Hospital, No. 786, Yuyuan Road, Changning District, Shanghai 200051, People’s Republic of ChinaTel +86-13661900956; +86-13661900280Email liupingshai@163.com; cbma1966@live.cnPurpose: Cervical squamous cell carcinoma (CSCC) seriously affects women’s health worldwide, and it is of great significance to illuminate the specific role of circRNAs in CSCC.Materials and Methods: Three mRNA datasets, two miRNA datasets and one circRNA dataset of CSCC, downloaded from GEO, were utilized in this study. Differentially expressed mRNAs (DEmRNAs), miRNAs (DEmiRNAs) and circRNAs (DEcircRNAs) were identified, and a ceRNA (DEcircRNA-DEmiRNA-DEmRNA) regulatory network was constructed. GO and pathway analyses of DEcircRNAs and DEmRNAs in the ceRNA regulatory network were performed. Quantitative real-time polymerase chain reaction (qRT-PCR) validation of the expression of the selected DEmRNAs, DEmiRNAs and DEcircRNAs was performed.Results: A total of 1356 DEmRNAs, 13 DEmiRNAs and 77 DEcircRNAs were obtained. The ceRNA network contained 3 circRNA-miRNA pairs and 158 miRNA-mRNA pairs, including 3 circRNAs, 3 miRNAs, and 138 mRNAs. Functional annotation of DEmRNAs in the ceRNA regulatory network revealed that these DEmRNAs were significantly enriched in cell cycle, p53 signalling pathway and DNA replication. The qRT-PCR results were generally consistent with those of our integrated analysis.Conclusion: In conclusion, we speculate that the regulation of the hsa_circ_0000069/hsa-miR-125b-5p/CDKN2A and hsa_circ_0020594/hsa-let-7c-5p/CCNB2 axes may be involved in CSCC.Keywords: cervical squamous cell carcinoma, CSCC, circRNA, ceRNA network, GEO